The potential of photovoltaics, Biomass and Mini - Hydro as Renewable energy - Amerul Affiq Bin Osman (2023)
In this era the side effect of burning of fossil fuel becoming major concern in worldwide. Malaysia also giving the effort in practising renewable energy in order to help mother nature. This paper reports the renewable energy resources and technology that have been practised in Malaysia. It also presents the present energy scenario, renewable energy resources and future prospect in Malaysia. For achieving growth and progress in a developing country, utilization of the available energy sources is of prime importance. Bangladesh is endowed with vast renewable energy resources such as biomass, photovoltaic, hydro plant and etc. Renewable energy resources cannot serve as the alternative to conventional energy, yet they may serve to supplement the long-term energy needs of the country. By 2030 energy demand in Malaysia will be more than double. So, depending only on the conventional energy sources will not solve the energy crisis. In Malaysia, there remains a slight discrepancy between urban and rural energy usage. With the potential of different renewable energy resources, Malaysia has been experiencing a gradual shift towards exploring renewable energy resources. Different renewable energy technologies project has been started to facilitate and increase the utilization of renewable energy resources for its advantages. This study indicates that using renewable energy sources as a supplement to the conventional energy sources can fulfil the ever-increasing demand in Malaysia future. This also include the disadvantage of adapting these renewable energy type. We will study the advantages and disadvantages of them regarding three most important aspect which are cost, efficiency and effect towards the environments. In the end of the study we can see that Biomass have quite high potential as becoming the main energy resources in Malaysia.